Intensive and Extensive Margins of Export: Determinants of Economic Growth in Russian Regions under Sanctions - Анна Андреевна Федюнина; Юрий Вячеславович Симачёв; Игорь Михайлович Драпкин (Экономика региона, 2023)
The impact of foreign trade on the Russian economy’s growth remains debatable. In 2014, the economy faced initial sanctions, leading to export restructuring and affecting growth. In 2022, a second unprecedented wave of sanctions necessitated export restructuring and intensified the challenge of sourcing economic growth. This study evaluates the impact of intensive and extensive export margins on Russian regions’ growth from 2015 to 2021 and discusses post-2022 implications. It is hypothesised that new export goods and markets are vital for economic growth in Russian regions. The study shows that both intensive and extensive margins are positively related to the level of development in Russian regions, and developed regions with diversified economic structures had higher values of export margins. The methodology uses panel regression with random and fixed effects. The empirical results show Russian regions’ market share in the products they export and in the countries where they export (i. e. intensive product and geographic margin) is important for the economic growth of Russian regions, while the results for extensive margin are ambiguous. The obtained findings have implications for industrial policy, which should prioritise the development of measures aimed at supporting existing exporting companies in expanding their presence in familiar markets. The task of export diversification should primarily be addressed through working with existing exporters and export products, while the export of innovative products should be viewed as a gradual evolutionary process within the framework of long-term planning.